2007
DOI: 10.1177/104063870701900418
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Diagnosis of Canine Ovarian Epithelial and Granulosa Cell Tumors

Abstract: In humans and canines, the morphology of granulosa cell tumors is extremely variable and causes diagnostic difficulties. In human pathology, immunohistochemistry has been widely used for the diagnosis of granulosa cell tumors, whereas, limited studies are present in canine species. The aim of this study was to investigate the expression of cytokeratins, vimentin, and inhibin-alpha in canine normal ovaries, epithelial ovarian tumors, and granulosa cell tumors to establish an immunohistochemical panel for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
5
34
0
1
Order By: Relevance
“…Using an antibody that detects a wide spectrum of cytokeratins (CK), positive reaction was found in neoplastic cells in our case; the finding is similar to other authors' observations (Costa et al 1994;Riccardi et al 2007). However, one of the cytokeratins, cytokeratin 7, is selectively expressed in healthy and neoplastic ovarian surface epithelium and is a useful immunohistochemical marker for the differentiation of epithelial ovarian tumours from granulosa cell tumours (Ramaekers et al 1990;Riccardi et al 2007). In our case there was a negative reaction for CK 7.…”
Section: Immunohistochemistrysupporting
confidence: 81%
See 3 more Smart Citations
“…Using an antibody that detects a wide spectrum of cytokeratins (CK), positive reaction was found in neoplastic cells in our case; the finding is similar to other authors' observations (Costa et al 1994;Riccardi et al 2007). However, one of the cytokeratins, cytokeratin 7, is selectively expressed in healthy and neoplastic ovarian surface epithelium and is a useful immunohistochemical marker for the differentiation of epithelial ovarian tumours from granulosa cell tumours (Ramaekers et al 1990;Riccardi et al 2007). In our case there was a negative reaction for CK 7.…”
Section: Immunohistochemistrysupporting
confidence: 81%
“…However, poorly differentiated granulosa cell tumours may be confused with ovarian epithelial tumours (Pelkey et al 1998;Riccardi et al 2007). Differentiation between these two types of tumours has great prognostic importance, since ovarian epithelial tumours are frequently malignant and metastatic (Riccardi et al 2007). Granulosa cell tumours usually stain positive for α-inhibin, vimentin and calretinin (Ashorn et al 1988;McCluggage and Young 2005;Riccardi et al 2007).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, simple co-expression of these two intermediate filaments cannot be used as a marker of neoplastic mesothelial cells, since co-expression of cytokeratin and vimentin in the same cells has been detected also in other types of tumors, for example synovial sarcomas, haemangiosarcomas, mammary gland carcinomas (Desnoyers et al 1990, Rabanal andElse 1994). Moreover, co-expression of cytokeratin and vimentin has also been found in tumors which, in cases of dissemination, can be included in differential diagnosis of visceral tumors, among them thyroid carcinomas, prostatic carcinomas, endometrial adenocarcinoma, ovarian epithelial tumors and mammary gland carcinomas (Grieco et al 2003, Riccardi et al 2007, Pires et al 2010. The study performed on the canine lung carcinomas has revealed co-expression of cytokeratin and vimentin in neoplastic cells in 38% of cases (Burgess and Kerr 2009).…”
Section: Discussionmentioning
confidence: 91%